PERANCANGAN SISTEM INFORMASI PENGELOLAAN PERSEDIAAN BAHAN KIMIA LABORATORIUM DI POLITEKNIK XYZ - Mukhsalmina Mukhsalmina; Adhy Prasetyo; Muhammad Ikhwan; Annisa Nukhikmat Al Basith; Gilang Alfurqoni Surya Kusuma Ningtyas (Politek ATK Yogyakarta Press, 2025)
The chemical inventory management system in the XYZ Polytechnic laboratory has not been optimally integrated, so real-time stock monitoring is still limited and has the potential to cause discrepancies between the amount of stock recorded and actual conditions. This inaccuracy in inventory management can hamper the smooth running of laboratory activities. This research aims to design a chemical inventory management information system using a prototype approach, which includes the stages of Communication, Quick Planning, Quick Modelling, Construction, and Deployment. The system was developed with Microsoft Access and Visual Basic for Applications (VBA) and designed with main components that include inventory recording and real-time stock monitoring. In addition, the system is also equipped with a feature to export stock data into systematic reports to support the analysis and reporting process. The results of testing the prototype show that the developed system is able to integrate the process of recording and monitoring stock in real-time, thus improving the accuracy of inventory data and efficiency in managing chemicals in the laboratory.